Perovskite Solar Cells: High‐Efficiency Low‐Temperature ZnO Based Perovskite Solar Cells Based on Highly Polar, Nonwetting Self‐Assembled Molecular Layers (Adv. Energy Mater. 5/2018). Issue 5 (15th February 2018) - Azmi, Randi; Hadmojo, Wisnu Tantyo; Sinaga, Septy; Lee, Chang‐Lyoul; Yoon, Sung Cheol; Jung, In Hwan; Jang, Sung‐Yeon
Abstract : In article number1701683, In Hwan Jung, Sung‐Yeon Jang, and co‐workers report the synthesis of 'high‐efficiency low‐temperature processed perovskite solar cells' by the combination of two techniques; the modification of solution‐processed ZnO using a self‐assembled monolayer, and the fabrication of perovskite layers by a sequential deposition method. This technique may pave the way to efficiently reducing the processing temperature of perovskite solar cells.